Penerapan Pendekatan Kontekstual Dalam Membangun Self Awereness Siswa Kelas VII SMP Katolik Rantepao - Selvy Rajuaty Tandiseru; Alexander Pakiding; Meliakin Pilipus (LPPM UKI Toraja, 2021)
The contextual approach is one of the learning strategies that emphasizes the processof full student involvement in being able to find material that is learned and connectswith real situations. This research is a descriptive study that aims to find out: 1) theimplementation of learning in applying a contextual approach: 2) student activities inmanaging learning with a contextual approach: 3) comparison of self-awareness of classVII students of Rantepao Catholic Middle School with the application of a contextualapproach. The population in this study were all seventh grade students of RantepaoCatholic Middle School consisting of a total of 86 students. The sampling technique iscluster random sampling technique, so that two classes were selected, namely class VIIcand VIIA as a sample with a total of 57 students. Data collection techniques used were two,namely observation and student self awareness questionnaire, using instruments in theform of observation sheets the ability of teachers to see how the teacher’s ability to managelearning, observation sheets of students to see how student activities during learning takeplace and student self awareness to see how build self awareness in mathematics learning.As a conclusion, it is stated that the application of a contextual approach in buildingstudent self awareness is used in the seventh grade mathematics learning of RantepaoCatholic Middle School.